Ameliorative role of mixed hydro-methanolic (60:40) extract of Andrographis Paniculata on chromium (VI)-induced immunomodulation in male albino rats (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
The immune system controls the body’s homeostatic state and helps to defend against infections. Activation and expansion of many biomolecules are crucial for the homeostatic state. Chromium, a common heavy metal found in nature, is an active in its hexavalent state. The abundant use of chromium in paints, steel plants, intoxicated the workers and modulates their body homeostasis. In this article, we were intended to evaluate the role of Andrographis paniculata Nees extract on restoration of the body homeostatic state in terms of immune system. For the present investigation, a group of male albino rats (80–100 g) were induced by intraperitonial injection of vehicle (0.9% NaCl), Potassium dichromate (K2Cr2O7) (0.8 mg / 100 g body weight / day), K2Cr2O7 plus mixed hydro-methanol solvent extract in the ratio of 60:40 at a dose of 500 mg/kg body weight daily at an interval of six hours after injection of K2Cr2O7 for a period of 28 days. We found that Cr (VI) induces a hyper response of pro-inflammatory cytokines followed by apoptosis in liver and lung tissue. Excess production of reactive oxygen species (ROS) is controlling the whole phenomena. The A. paniculata Nees extract successively inhibit the ROS generation, as a result a significant quenching of pro-inflammatory cytokine production was noted. A. paniculata Nees extract prompted decrease amount of ROS and its associated inflammation provoke the cell survival and helps to maintain a homeostatic state of the body.